The prehistory of Asia Minor : from complex hunter-gatherers to early urban societies - Düring, Bleda S., (Cambridge University Press, 2011)
"In this book, Bleda Düring offers an archaeological analysis of Asia Minor, the area equated with much of modern-day Turkey, from 20,000 to 2,000 BC"-- Provided by publisher.